Delayed union of a pediatric lunate fracture in the United Kingdom: a case report and a review of current concepts of non-scaphoid pediatric carpal fractures - Timothy P. Davis; Elizabeth Headon; Rebecca Morgan; Ashley I. Simpson (Journal of Trauma and Injury)
Pediatric carpal fractures are rare and often difficult to detect. This paper reviews the current literature on pediatric non-scaphoid carpal fractures, with a case report of a lunate fracture associated with a distal radius and ulnar styloid fracture, managed nonoperatively in a 12-year-old boy. There is lack of consensus regarding the management of these fractures due to the low number of reported cases. A frequent lack of long-term follow-up limits our understanding of the outcomes, but good outcomes have been reported for both nonoperative and operative management. This case report brings attention to the current time period for the definition of delayed union in pediatric carpal fractures, and emphasizes the need for prolonged follow-up for the detection of delayed complications leading to functional impairment.